Antibiogram patterns of staphylococcus aureus obtained from packaged meat, milk and milk products, fruits and vegetables of various supermarkets in Dhaka city - Hussain, Benazir Khandaker (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2017.